2012
DOI: 10.1105/tpc.111.093302
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies for 21st Century Plant Science

Abstract: Plants are one of the most fascinating and important groups of organisms living on Earth. They serve as the conduit of energy into the biosphere, provide food, and shape our environment. If we want to make headway in understanding how these essential organisms function and build the foundation for a more sustainable future, then we need to apply the most advanced technologies available to the study of plant life. In 2009, a committee of the National Academy highlighted the "understanding of plant growth" as on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 187 publications
(179 reference statements)
0
38
0
Order By: Relevance
“…VA-TIRFM is a type of microscopy that takes advantage of the unique property of the evanescent wave produced at the interface between the specimen and a glass coverslip and confines the excitation of the fluorophores to a depth of 100-400 nm in the specimen (Mattheyses et al, 2010;Wan et al, 2011). This provides a powerful approach to clarify spatially the details of complex kinetics at the single-molecule level in living plant cells (Ehrhardt and Frommer, 2012). From VA-TIRFM observations, we found that AP2 σ-EGFP formed discrete foci at the plasma membrane.…”
Section: Research Articlementioning
confidence: 99%
“…VA-TIRFM is a type of microscopy that takes advantage of the unique property of the evanescent wave produced at the interface between the specimen and a glass coverslip and confines the excitation of the fluorophores to a depth of 100-400 nm in the specimen (Mattheyses et al, 2010;Wan et al, 2011). This provides a powerful approach to clarify spatially the details of complex kinetics at the single-molecule level in living plant cells (Ehrhardt and Frommer, 2012). From VA-TIRFM observations, we found that AP2 σ-EGFP formed discrete foci at the plasma membrane.…”
Section: Research Articlementioning
confidence: 99%
“…Very few reports exist of the study of cellular structures with such high resolution in plant samples due to numerous technical challenges, 44 including the generally high fluorescence background due to significant autofluorescence of endogenous components, and the presence of the cell wall (> 250 nm thickness). The former leads to low signal to noise ratio (S/N) for single molecule detection and therefore low localization accuracy and low spatial resolution.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…25,43 Quantitative analysis of microtubule organization can therefore provide insight into the expansion and differentiation status of cells within the root. 44 Due to technical limitations, the details of microtubule structures have not been fully visualized or quantified.…”
Section: Quantitative Analysis Of the Microtubule Network With Sub-50mentioning
confidence: 99%
“…Given the impending changes in demography and rise in related problems for food, fodder and fuel under the climate change scenarios, it is time to invent and apply new and faster technologies towards crop improvement. Hence, modern, high-throughput platform technologies are increasingly being applied to obtain information at different molecular levels e.g., RNA transcript, protein and metabolite at the plant systems level (Ehrhardt and Frommer 2012). Of these technologies, we will discuss here the proteomics technology and its utilization in India and Nepal which is contributing substantially to better understand the plant systems.…”
Section: Addressing the Issues And Where We Arementioning
confidence: 99%